PENGARUH PEMAHAMAN SISWA TENTANG KONSEP BUDAYA POLITIK TERHADAP KARATERISTIK ASPIRASI PEMILIH PEMULA DI SMA AL-KAUTSAR KOTA BANDAR LAMPUNG - Tubagus Ali Rachman Puja Kesuma (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
Political education is something that is very important to invest in the youth moslem at SMA Al- Kautsar Bandar Lampung, especially in class XI and XII were an average age of 17 years as well as a first-time voters. Therefore civic education curriculum subjects in class XI mandated political learning, and one of them through the material political culture. The purpose of this study was to describe the influence of students’ understanding of the concept of political culture on the characters of the political aspirations of the voters in SMA Al-Kautsar Bandar Lampung. This research method is descriptive correlational, the population in this study were all students in Al-Kautsar Bandar Lampung who have become voters that amounted to 271 people, while the sample is 25% of the population of 68 people and taken with Proportional Stratified Random Sampling technique. Data collection techniques used is to test and questionnaire were then performed data processing and analysis using statistical program SPSS version 17.00. Understanding of the students in understanding the concept of political culture affect the level of the political aspirations of the students, It is based on the calculation of the path coefficient r> 0 is obtained r1 = 0665 with signification 0,509 and significance of the aforementioned significance level a = 0:05 there by variables influence positively and significantly. It means that to raise the aspirations of voters in the school can be done with the political culture of learning properly. the better the learning of political culture that carried the better also aspiration level students.